Natural Deep Eutectic Solvents: A New Environment Friendly Solvent - Saurabh Kumar Tiwari; Pratibha Yadav; Mrigank Mauli Dwivedi; Pandey, Kamlesh (New Environmentally-Friendly Materials, 2026)
The fabrication of materials and chemical synthesis depend substantially on solvents. They are strategic part of the green chemistry framework. In accordance with green chemistry, solvents need to qualify certain parameters, such as biodegradability, non-toxicity, non-flammability, recyclability & reusability, low cost etc. to be termed as green solvents. Deep eutectic solvents (DESs) are emerging as excellent “designer” alternatives to conventional solvents owing along with the above mentioned eco-friendly properties have exceptional thermal, moisture durability and best tunable features. DESs have a crucial role in several field related to chemical synthesis along with catalysis, material extraction and purification. They serve an array of roles as solvents, monomers, and templating agents. The Deep Eutectic Solvent (DES)-based electrodeposition opens a new era of the development of metal, alloy, and metallic nanocomposite coatings with highly tailored properties. The corrosion resistance of these coatings is multifactorial, dictated by the DES composition, metal ion concentration, and precise electrochemical parameters. The Electrolytes based on DES are also useful and inexpensive replacements for traditional corrosive and environmentally hazardous aqueous acid solutions for metal alloy electropolishing. In this current review, we are providing an overview of recent research on DES in polymer synthesis and material fabrication.